Novel DC arc plasma method for super dispersed metal carbides synthesis; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Pak A. Ya. Aleksandr Yakovlevich (2021, 2021)
Title screen